Analysis on the historical transformations of the beach of AvenidaMaceió/AL / Análise sobre as transformações históricas da praia da AvenidaMaceió/AL - Alesson Massalino da Silva; Elielson Batista Gonçalves; Erick Phelipe Ramos dos Santos; Kreslerson Carlson Alves de Gouveia; Cirlene Jeane Santos e Santos (Universidade Estadual de Alagoas, 2018)
The beach of the Avenue in the city of Maceió-AL, in the Center, for two months came from being the research target students of Bachelor's degree in geography, from the Universidade Federal de Alagoas (UFAL). The Group an attempt was made to perform an analysis of the landscape from the beach with the help of the perceptions of people residing in the nearby state capital and time to know the location. Through the review of historical documents and the implementation of an online questionnaire, on Google, search members sent the links through the internet communication applications so that the audience could respond if questioned. After reviewing the documents, out performed the analysis of the information obtained from the questionnaires, noting the observation with the reality. The questionnaire was answered by 50 informants, the same being composed of 10 variables, 6 quantitative and qualitative 4 character.